Тhere is hell, and then there is hell, or semantic and pragmatic analysis of A. Solzhenitsin’s, V. Shalamov’s and S. Dovlatov’s «camp prose» - GAZAROVA, DIANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article provides the characteristics of the notion «camp prose», points out its features in works of these three authors. All of three authors consider camp as hell, at the same time the semantic and pragmatic analysis of their works reveals their differentattitude to the camp experience.
Keywords: «camp prose», lexical peculiarities, one-member sentences, ellipsis, rhetorical question, parenthetical words